Induction of Primordial Germ Cells from Pluripotent Epiblast - Ying Ying; Xiaoxia Qi; Guang-Quan Zhao (The Scientific World Journal)
The formation of germ cells during embryogenesis bears the ultimate importance for the continuation of every species. It becomes evident that mechanisms governing germ cell fate specification are not well conserved across the animal kingdom. In most of the invertebrate and nonmammalian vertebrate species, certain maternally derived factors are key to the establishment of germ cell lineage. In contrast, mouse primordial germ cells (PGCs) are induced from the pluripotent epiblast cells before and during gastrulation by the extraembryonic cell-derived signals. The molecular identity for some of these signals has recently been revealed by genetic and epiblast culture experiments. Both bone morphogenetic proteins 4 (Bmp4) and 8b (Bmp8b) are expressed in the extraembryonic ectoderm and are required for PGC formation. Furthermore, BMP4 or BMP8B alone are unable to induce PGCs from cultured epiblasts, while they can in combination, indicating they signal through separate receptor complexes. In addition, Bmp4 homozygous embryos cannot be induced to form PGCs by the synergistic action of BMP4 and BMP8B, suggesting that BMP4 proteins produced by pregastrula embryos are required for epiblast cells to maintain pluripotency. Moreover, Bmp2, a close relative of Bmp4, is expressed in visceral endoderm at the time of PGC specification, and inactivation of Bmp2 results in a reduction in PGC number, revealing a novel function of visceral endoderm in PGC generation in the mouse.